Lesson study and 21st-century skills: Pre-service Teachers Reason, Produce and Share - Yeşilçınar, Sabahattin; Aykan, Ahmet (Ozgen Korkmaz, 2021)
Being a collaborative professional development model and contributing to the collaboration and communication skills of the group members, lesson study was coined in Japan and has been applied in many countries since then, which supports and enhances the professional development of teachers or pre-service teachers. Although literature abounds in studies on lesson study or on 21st-century skills, there is no study examining the impact of lesson study on 4Cs. Therefore, adopting an intrinsic case study approach, this paper examined to what extent a lesson study implementation influenced pre-service teachers’ 21st-century skills in the Turkish context where lesson study is not an embedded tradition. Participants were six senior students of English language teaching. The data generated were wide-ranging: recordings of meetings, teachers’ in-class observation notes, 4Cs checklist, recorded pre-and post-interviews, lesson study observation forms, and post-lesson evaluation forms. Findings showed that 21st-century skills of preservice teachers were developed, and pre-service teachers started to REASON the issues they face in the classroom, PRODUCE alternative way(s) to overcome troubles or support learning, and SHARE their experiences and solutions with colleagues sincerely in a collaborative atmosphere. However, one intriguing finding is that, in a context which does not embed lesson study, if the process is not internalized, it may cause the future teachers to be loath to reason, produce and share due to the lack of self-efficacy as well as the fear of being criticized. © 2021, Ozgen Korkmaz. All rights reserved.
Keywords: 21st-century skills; Lesson study; Practicum; Professional development